ANALISIS KEPUASAN PASIEN TERHADAP APLIKASI HARYOTO ONLINE DENGAN MENGGUNAKAN METODE EUCS - Rachman, Mohammad Arief; Fitroh Lisya Farasi, Febriannisa (Malang: Sekolah Tinggi Ilmu Administrasi Malang, 2024)
User satisfaction refers to the satisfaction felt by a user with a particular product, service, or experience. A person's satisfaction is simply formed by two components, namely the user's expectations of a product compared to the value the product has provided to the user. The purpose of this study was to determine patient satisfaction in using the Haryoto Online application using the End User Computing Satisfaction (EUCS) model. This study uses a descriptivemethod with a quantitative approach with a questionnaire instrument. Data collection was carried out by distributing questionnaires to 45 respondents using the Haryoto online application who use and utilize the application. The results show that in the ease of use dimension the patient is very satisfied, in the format, content and accuracy dimension the patient is satisfied and in the timeliness dimension the patient is neutral.